2021
DOI: 10.1021/acs.jchemed.1c00181
|View full text |Cite
|
Sign up to set email alerts
|

Remote Chemistry Teacher Professional Development Delivery: Enduring Lessons for Programmatic Redesign

Abstract: COVID-19 has thrust educators into a period of uncertainty, complicating conventional ways of teaching and learning. We suspect that the pandemic has magnified the challenges that some high school teachers already experience, particularly when they are the sole chemistry teacher at their school. The pandemic has likely inhibited collegial interactions and access to professional development (PD). Our reflections from redesigning a face-to-face PD program to one that is remotely delivered provide recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…This project was also helpful for them to understand science projects aligned with NGSS, phenomena-based learning, and 5E instructional models. The findings were similar to a recent study about a remote professional development program for high school chemistry teachers during the pandemic, which showed that the participants provided positive feedback on the professional development program …”
Section: Resultssupporting
confidence: 88%
“…This project was also helpful for them to understand science projects aligned with NGSS, phenomena-based learning, and 5E instructional models. The findings were similar to a recent study about a remote professional development program for high school chemistry teachers during the pandemic, which showed that the participants provided positive feedback on the professional development program …”
Section: Resultssupporting
confidence: 88%
“…Information regarding our setting and sampling process is described in greater detail in a previous article. 62…”
Section: ■ Pedagogical Chemistry Sensemaking: a Theoretical Lens To A...mentioning
confidence: 99%
“…After the forms had been submitted, the research team developed a weighted ranking system that prioritized applicants who described more student-centered practices, taught at schools with higher percentages of students who qualified for the federal reduced/free lunch programs, and possessed 2–20 years of teaching experience (enough to understand chemistry content but early enough in their careers for the PD to have a longer impact on students). Information regarding our setting and sampling process is described in greater detail in a previous article …”
Section: Settingmentioning
confidence: 99%
“…The VCI has currently been implemented in July 2020 (n = 20) and 2021 (n = 16) as four full days and seven half days each, resulting in 28 hours of PD for each teacher. Information regarding the PD's design and sampling procedure has been summarized in a previous paper (Wu et al, 2021). All protocols related to sampling, PD, and teacher artifact collection/analysis have been approved by the institutional review board of the hosting university.…”
Section: Contextualizing Pedchemsensementioning
confidence: 99%